Foraging Activity and Species Composition of Ants during Day/Night in Primary and Secondary Forests in Papua New Guinea - Lenc, Jan (Jihočeská univerzita, 2023)
This study examines diel foraging activity and species composition of vertically stratified ant communities between primary and secondary forests in Papua New Guinea. To determine the diel foraging activity and changes in species composition of ants, the abundance was estimated/approximated from baits on tree trunks or the forest floor.
Foraging activity and species composition of ants during day/night in primary and secondary forests in Papua New Guinea
Keywords: ants; diel foraging activity; environmental gradients; Papua New Guinea; temporal stratification.; ants; diel foraging activity; environmental gradients; Papua New Guinea; temporal stratification.